Assessing a novel contact heater as a new method of recovering explosives traces from porous surfaces - Yu, H.; Lewis, Simon; Beardah, M.; NicDaeid, N. (Elsevier, 2015)
It can be very challenging to recover explosives traces from porous surfaces, such as clothing and car seats, compared to non-porous surfaces. The contact heater has been developed as a novel instrument designed to recover explosives traces from porous surfaces. Samples are taken by heating and drawing air across a surface, with the air flowing through a sampling cartridge containing adsorbent polymer beads, which act to trap any recovered explosive material. Any collected explosive can then be eluted from this cartridge using a solvent, prior to analysis. This paper outlines work performed to evaluate the usefulness of the contact heater with regards to the recovery of explosives traces from porous materials. Ethylene glycol dinitrate (EGDN) and triacetone triperoxide (TATP) were chosen as two representative explosives for this study. Quantification was performed using GC–MS for EGDN and LC–MS/MS for TATP. Different sampling temperatures, sampling times and elution solvents were investigated. Recovery was trialled from leather, carpet and denim. Recoveries of up to 71% were obtained following optimisation. It was also possible to recover TATP from fabrics exposed to TATP vapour in a vapour-laden jar up to two hours after exposure. The contact heater therefore appears to be a very useful tool for the recovery of explosives traces from porous materials.